Interpretation and grammar interaction in the Spanish subjunctive adjuncts - Sanchez-Naranjo, Jeannette (Borealis – An International Journal of Hispanic Linguistics, 2014)
This article proposes a multifactor analysis of the Spanish subjunctive adjuncts. By examining the features that govern Spanish mood and their interaction, I present a complete overview of diverse accounts on the Spanish subjunctive. I outline the general principles of those explanations and comment on their advantages and disadvantages in formalizing an explanation concerning the interaction of mood with syntax, semantics, and pragmatics. Next, from mood contribution to the flow in discourse, based on Quer’s (1998, 2001) approach, I provide a role for the subjunctive mood in the discourse, which can be established by a variety of factors. Instead of assigning rigid meanings to the subjunctive, this approach allows the speaker to relate the proposition to the actual world and provide an evaluation of it. In addition to this, I present a proposal to explain mood alternation in adjuncts considering the interaction of different components of the grammar in the process of interpretation. This contribution offers a dynamic view of meaning in which context and individuals are crucial for the interpretation of the Spanish subjunctive.